Pengaruh Kematangan Emosional terhadap Kesiapan Menikah pada Perempuan Dewasa Awal di Kota Samarinda - Sabrina Sabrina; Yoga Achmad Ramadhan; Silvia Eka Mariskha (International Forum of Researchers and Lecturers, 2026)
Readiness for marriage in young adult women is becoming an increasingly important issue due to the increasing trend of delaying marriage and the high demands of individuals to prepare themselves before entering family life. One of the psychological factors suspected to play a role in shaping readiness for marriage is emotional maturity, namely the ability of individuals to control emotions, adapt, and make mature decisions. This study aims to determine the effect of emotional maturity on readiness for marriage in young adult women in Samarinda City. This study uses a quantitative approach with 100 early adult women aged 20-30 years selected using a purposive sampling technique. Data collection was carried out using the Emotional Maturity Scale based on Singh and Bhargava's theory and the Marriage Readiness Criteria scale based on Ghalili's theory, then analyzed using simple linear regression with the help of SPSS version 26. The results of the study indicate that emotional maturity has a positive and significant effect on readiness for marriage (p < 0.001) with a contribution of 26.1% (R2 = 0.261). These findings indicate that the higher the emotional maturity of an individual, the higher the readiness for marriage in early adult women in Samarinda City.